Aktivitas Antioksidan dan Profil Sensori Minuman Sari Kacang Merah (Phaseolus vulgaris L.) dengan Penambahan Ekstrak Jahe Merah - Pandiansyah, Ahmad; Asiah, Nurul; Ramadhan, Kurnia; Ardiansyah, Ardiansyah (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2024)
The diversification and product development of kidney bean and ginger products have not yet been fully explored, especially in relation to antioxidant activity and sensory profiles. This study aims to evaluate the antioxidant activity, total phenolic compounds (TPC), sensory profile, and consumer acceptance of a kidney bean drink with added red ginger extract. Three variations of the kidney bean drink were tested, each containing different concentrations of red ginger extract: 0, 4, and 8%. Antioxidant activity was measured using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method, while TPC was determined using the Folin Ciocalteu method. Sensory analysis was conducted using the free choice profiling (FCP) method, with results analyzed through generalized procrustes analysis (GPA) to identify the sensory characteristics of the samples. Additionally, a hedonic test was used to assess the level of panelists' preference for each sample. The results showed that the addition of red ginger extract significantly affected (p